1998
DOI: 10.1123/ijsn.8.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Nutrient Intakes of the United States National Women's Artistic Gymnastics Team

Abstract: The nutrient intakes and dietary practices of elite, U.S. national team, artistic female gymnasts (n = 33) were evaluated using 3-day food records. The gymnasts' reported energy intake was 34.4 kcal/kg (total 1,678 kcal/day), which was 20% below the estimated energy requirement. The contributions of protein, fat, and carbohydrate to total energy intake were 17%, 18%, and 66%, respectively. All reported vitamin intakes, except vitamin E, were above the RDA. The reported mineral intakes, especially calcium, zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 0 publications
2
24
1
8
Order By: Relevance
“…Vitamin intakes in female athletes are typically above the recommendations, but not very much higher than in untrained females 28,30,33,53,[57][58][59][60][61] . Several studies have found low iron 28,30,53,[57][58][59][60][61] , zinc 30,59,62 and copper 28 intakes in both female athletes and controls. However, these results may at least partly be explained by underreported dietary intake 63 .…”
Section: Dietary Intake -A Balancing Factor?mentioning
confidence: 99%
“…Vitamin intakes in female athletes are typically above the recommendations, but not very much higher than in untrained females 28,30,33,53,[57][58][59][60][61] . Several studies have found low iron 28,30,53,[57][58][59][60][61] , zinc 30,59,62 and copper 28 intakes in both female athletes and controls. However, these results may at least partly be explained by underreported dietary intake 63 .…”
Section: Dietary Intake -A Balancing Factor?mentioning
confidence: 99%
“…Vitamin C intake in four other studies was only marginally better than the recommended intake of 60 mg/day (Ersoy, 1991;Lindholm et al, 1995;Moffatt, 1984;Short & Short, 1983). In two surveys of 7-to 10-year-old and 11-to 14-year-old gymnasts, the intake of vitamin C was approximately double the recommended level for age and gender (Benardot et al, 1989;Jonnalagadda et al, 1998).…”
Section: Calciummentioning
confidence: 99%
“…Vitamin B2 (Ribofl avin) With the exception of two surveys (Benardot et al, 1989;Jonnalagadda et al, 1998), all other nutrient intake studies dysfunction of reproductive hormones occurs below 20-30 kcal/kgLBM/day of energy availability (energy consumed minus exercise energy expended in training). Amenorrhea is now considered the most serious clinical problem associated with abnormal bone development (Roupas & Georgopoulos, 2011).…”
Section: Vitamin B1 (Thiamin)mentioning
confidence: 99%
“…Nutritional assessments of young female gymnasts indicate that many of these girls have an intake which is less than the usual recommended dietary allowance (DRI 2002) for their age and physical activity level (Jonnalagadda et al 1998;Fogelholm et al 1995;Cupisti et al 2000;Weimann et al 1999). Female gymnasts require grace and the ability to achieve rapidly coordinated movements, which necessitates a lean body.…”
Section: Introductionmentioning
confidence: 97%